Proceedings of the 8th International Conference on Interaction Design and Children 2009
DOI: 10.1145/1551788.1551804
|View full text |Cite
|
Sign up to set email alerts
|

How children search the internet with keyword interfaces

Abstract: Children are among the most frequent users of the Internet, yet searching and browsing the web can present many challenges. Studies over the past two decades on how children search were conducted with finite and predetermined content found in CD-ROM applications, online digital libraries, and web directories. However, with the current popularity of the open Internet and keyword-based interfaces for searching it, more critical analysis of the challenges children face today is needed. This paper presents the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
102
3
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 102 publications
(124 citation statements)
references
References 21 publications
13
102
3
6
Order By: Relevance
“…Given that most of our findings are in-line with previous studies of children's information-seeking behavior [5,6,7,13], we consider that this work represents a valuable and well-suited methodology to study the search behavior of users retrieving information for children. Although these case-studies are highly valuable for the understanding of user's behavior, the characterization of users on a large-scale using query logs has several advantages: It is unobtrusive (which makes possible to capture the actual user behavior), safer, repeatable, non-disruptive, non-reactive, inexpensive, a resource of longitudinal data (accessibility over long periods of time) and it allows the design and evaluation of solutions in realistic scenarios.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Given that most of our findings are in-line with previous studies of children's information-seeking behavior [5,6,7,13], we consider that this work represents a valuable and well-suited methodology to study the search behavior of users retrieving information for children. Although these case-studies are highly valuable for the understanding of user's behavior, the characterization of users on a large-scale using query logs has several advantages: It is unobtrusive (which makes possible to capture the actual user behavior), safer, repeatable, non-disruptive, non-reactive, inexpensive, a resource of longitudinal data (accessibility over long periods of time) and it allows the design and evaluation of solutions in realistic scenarios.…”
Section: Discussionsupporting
confidence: 81%
“…The frequency of these type of queries are summarized in Table 2. In this table is shown that question queries are more frequent in the children queries (queries use to retrieve information for children) than in the general purpose query set, which is in line with Druin's observations [13].These findings suggest that query reduction and query segmentation techniques can be particularly beneficial for children content queries since it has been shown that longer queries are less efficient [23]. Similarly query reformulation techniques based on morphological and syntactical features of the queries can improve the search process by mapping phrases to concepts and keywords [14].…”
Section: Query Type Analysissupporting
confidence: 86%
See 3 more Smart Citations